Determination of Organic Acids in Tobacco by Reversed Phase Liquid Chromatography - Jin, Xiao-Yan; Guo, Jun-Cheng; Cheng, Xiao-Lei; He, Hei-Hui; Yan, Xiang-Yang (Asian Journal of Chemistry, 2010)
A reversed phase liquid chromatography separation method with ultraviolet detection has been developed for the determination of organic acids in tobacco. The gradient mobile phase employed was 20 mM phosphate buffer (pH = 2.6) and acetonitrile at a flow-rate of 1.0 mL/min. All organic acids were eluted in less than 16 min. Target compounds were detected at 210 nm. Limits of detection (LOD) for the 11 acids ranged from 0.0007-1.419 mM and recoveries between 84.2-106.3% were found. Reproducibility (RSD) was better than 2.5% for retention times and between 0.42 and 1.78% for peak areas.